Perpetrators and Accomplices: A Comparative Study Between the German Penal Code and the American Model Penal Code - Cordini, Nicolás Santiago (2024)
For more than a hundred years, the study of the parties involved in a crime has been extensively researched, becoming a crucial topic in the field of criminal law. Although there is a considerable amount of research on this issue in the common law and civil law systems, there has been a notable lack of interest in comparative law studies between the two systems. This paper presents a comparative law study between the aforementioned models, offering a parallel and analytical analysis to understand their application and the challenges associated with the implementation of these categories. These categories are increasingly universal in Western criminal thought and policy, which makes this analysis systematic, complex and articulated. The analysis will focus on the German Criminal Code interpreted in the light of the theory of the act dominion and the Model Penal Code, serving as a harmonizing instrument for various criminal codes prevailing in the U.S. The need for comparative studies on U.S. criminal law and the German Criminal Code will be highlighted. With the internationalization of criminal law, comparative studies are becoming indispensable, as it is in this area that the clash of legal cultures occurs. A comparative study between the two models aims to determine the extent to which each system has similarities and differences. This study seeks to provide a deeper understanding of the similarities and differences between the systems of the Model Penal Code (common law) and the German Penal Code (civil law) with the aim of exposing the extent to which they differ and, thus, to improve the application of criminal categories in a context of internationalization.